Identification and characterization of geological formations with CO2 storage potential in Portugal - Pereira, Pedro; Ribeiro, Carlos; Carneiro, Júlio (Petroleum Geoscience, 2021)
Carbon capture, utilization and storage (CCUS) is considered a major part of the Portuguese strategy for reducing CO2 emissions. Some industrial sectors, the most prominent being the cement sector, require the implementation of CO2 storage to reach carbon neutrality by 2050. This paper presents and characterizes the areas with potential for CO2 storage in mainland Portugal. The lithostratigraphic and tectonic frameworks of the onshore and offshore basins are presented; a site screening process was conducted, based on basin- and regional-scale assessments, resulting in the definition of eight possible storage clusters, seven of which are offshore. The storage capacity was estimated for those clusters, with a central (P50) value of 7.09 Gt; however, the most interesting locations are in the Lusitanian Basin (West Iberian Margin), both onshore and offshore, as they present high capacity and are located favourably in relation to the industrial CO2 emitters. Considering only the potential sites of this basin, their storage capacities are greater than 3 Gt CO2, of which 260 Mt are onshore.
Keywords: storage capacity; storage units; sedimentary basins; caracterization